The importance of dietary change for men diagnosed with and at risk of prostate cancer: a multi-centre interview study with men, their partners and health professionals - Avery, Kerry NL (BioMed Central, 2014)
BACKGROUND: The diagnosis of prostate cancer (PC) can provide a trigger for dietary change, and there is evidence that healthier diets may improve quality of life and clinical outcomes. However, men’s views about dietary change in PC survivorship are largely unknown. This multi-centre qualitative interview study explored men’s views about dietary change in PC survivorship, to better understand motivations for, and barriers to, achieving desired changes. The role of radical and active surveillance treatments on dietary change and the influence of men’s partners were examined. Focus groups also evaluated stakeholder opinion, including healthcare professionals, about the provision of dietary advice to PC patients. METHODS: A multi-centre interview study explored views about diet and motivations for, and barriers to, dietary change in men at elevated risk or diagnosed with PC following prostate specific antigen (PSA) testing. 58 men and 11 partners were interviewed. Interviews and focus groups were undertaken with 11 healthcare professionals, 5 patients and 4 partners to evaluate stakeholders’ opinions about the feasibility and acceptability of providing dietary advice to PC patients. Data were analysed using methods of constant comparison and thematic analysis. RESULTS: Over half of diagnosed men reported making dietary changes, primarily to promote general or prostate health or facilitate coping, despite their uncertainty about diet-PC links. Interest in dietary advice was high. Information needs varied depending on treatment received, with men on active surveillance more frequently modifying their diet and regarding this as an adjunct therapy. Men considered their partners integral to implementing changes. Provision of dietary advice to men diagnosed with PC was considered by healthcare professionals and men to be feasible and appropriate in the context of a holistic ‘care package’. CONCLUSIONS: Many men make positive dietary changes after PC diagnosis, which are perceived by men and their partners to bring psychological and general health benefits and could help future dietary intervention trials. Men and their partners desire more and better dietary information that may support PC survivorship, particularly among those embarking on active surveillance/monitoring programmes. There are opportunities for healthcare professionals to support PC patients both clinically and psychologically by the routine integration of healthy eating advice into survivorship care plans.